Mengaburnya Ruang Publik dan Ruang Privat dalam Praktik Konsumsi Media Baru - Risky Wahyudi; Heru Nugroho (Jurnal Komunikasi, 2022)
The boarding room is a private room for students, but it is constantly changing due to the development of communication technology. This research shows that the media have found a barrier between the public and the private. By using the spatial ethnography method, this study finds that media consumption in boarding rooms has an impact on the way the occupants condition the private space zone. Data was collected by observation and interviews. The discussion is carried out by conducting a dialogue with field findings with the study of bedroom culture, which is offered by Siân Lincoln. This concept assumes that when young people (red: students) consume media in private spaces, they are actually at the crossroads between public and private. The findings of this study reveal that the presence of media in boarding rooms can open communication portals, thus giving rise to various mediated activities. This has made the boarding room an integral space, as well as a center for student activities. The student, when consuming media, can arrive at the reality of the world between the physical and the virtual world. This opens up opportunities for activities and controls that were previously public to enter their boarding rooms.